Pre-Pegmatite Stage in Peralkaline Magmatic Process: Insights from Poikilitic Syenites from the Lovozero Massif, Kola Peninsula, Russia - Julia A. Mikhailova; Yakov A. Pakhomovsky; Olga F. Goychuk; Andrey O. Kalashnikov; Ayya V. Bazai; Victor N. Yakovenchuk (Minerals, 2021)
The Lovozero peralkaline massif (Kola Peninsula, Russia) is widely known for its unique mineral diversity, and most of the rare metal minerals are found in pegmatites, which are spatially associated with poikilitic rocks (approximately 5% of the massif volume). In order to determine the reasons for this relationship, we have investigated petrography and the chemical composition of poikilitic rocks as well as the chemical composition of the rock-forming and accessory minerals in these rocks. The differentiation of magmatic melt during the formation of the rocks of the Lovozero massif followed the path: lujavrite → foyaite → urtite (magmatic stage) → pegmatite (hydrothermal stage). Yet, for peralkaline systems, the transition between magmatic melt and hydrothermal solution is gradual. In the case of the initially high content of volatiles in the melt, the differentiation path was probably as follows: lujavrite → foyaite (magmatic stage) → urtitization of foyaite → pegmatite (hydrothermal stage). Poikilitic rocks were formed at the stage of urtitization, and we called them pre-pegmatites. Indeed, the poikilitic rocks have a metasomatic texture and, in terms of chemical composition, correspond to magmatic urtite. The reason for the abundance of rare metal minerals in pegmatites associated with poikilitic rocks is that almost only one nepheline is deposited during urtitization, whereas during the magmatic crystallization of urtite, rare elements form accessory minerals in the rock and are less concentrated in the residual solution.